Meta-Pharmacologic Support and Scaffolding for Obesity Therapy - Sanjay Kalra; Nitin Kapoor; Saurabh Arora (Journal of the Pakistan Medical Association, 2026)
Obesity is a multifactorial endocrine disease. Novel hormone receptor modulators are now available for its treatment. This does not mean, however, that obesity can be managed or cured by pharmacotherapy alone. Multidimensional support and scaffolding are required to attain and sustain optimal outcomes with drug therapy. In this communication, we provide a systematic coverage of the various aspects of support that are needed. We term them metapharmacologic, as they extend beyond the realm of conventional pharmacology. These include biomedical (medical, endocrine, pharmacotherapeutic), lifestyle (nutrition, physical activity), and psychosocial (psychological, social, systemic) optimization. Keyword: Holistic care, Lifestyle medicine, nonpharmacological care, overweight, obesity, person-centred care